Website Design and Trust Elements: A/B Testing on a Start-up's Website - Lars Schmitt; Isabel Haupenthal; Faisal Bin Ahmed (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Start-ups are young companies that are hardly known, especially during their early stages, by the relevant stakeholders. A start-up's website is, therefore, often the first point of contact for potential customers, investors, or partners. Such a website usually explains the new product or service and presents the founding team with its competencies. The user's perception of the website and its design can be crucial in determining whether the user is interested in getting in touch with the start-up or even considering the purchase of the respective product or service. User's trust in the website and its operator is essential for this. The so-called trust elements, such as logos, testimonials, or seals, are intended to create trust on websites. So far, the influence of these elements on user behaviour has hardly been empirically proven in a real-life context. Therefore, we have applied the method of A/B testing to the website of a fictive start-up. Trust elements were placed on one variant of the website (A), whereas on the other variant, there were none (B). The experiment shows that the duration of the user sessions does not differ between the two variants. However, more requests were made on the website variant with trust elements.
Keywords: L26; C99; 330; website design; e-trust; online trust; e-commerce; A/B testing